Verifikasi Lokus Aluminum Tolerance (Alt) pada Tiga Populasi BC3F1 Padi - Mizan, Muhammad Rauful; Wirnas, Desta; Prasetiyono, dan Joko (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
Most of marginal lands in Indonesia are in the form of acid dry land with low available P and high Al concentrations. Development of tolerant rice varieties to P deficiency and Al toxicity is one way to increase rice production. This study aimed to select BC3F1-Pup1+Alt genotypes from three crosses based on foreground and background markers. This research was conducted at the Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development, Bogor, from August to December 2015. The materials used were 300 genotypes of BC3F1 Dodokan-Pup1+Alt, BC3F1 Situ Bagendit-Pup1+Alt, BC3F1 Batur-Pup1+Alt, and the parents. The research included selection in modified Yoshida’s nutrient solutions (0.5 ppm P dan 60 ppm Al) followed by foreground selection and background selection. Selection using Yoshida’s nutrient solution resulted in 150 genotypes with longer root than the recipient parent in each of the BC3F1 populations. Selection with foreground markers using markers RM1361 and RM12031 produced 85 genotypes of BC3F1 Dodokan-Pup1+Alt (56.6%), 105 genotypes of BC3F1 Situ Bagendit-Pup1+Alt (70%), and 77 genotypes of BC3F1 Batur-Pup1+Alt (51.33%). Selection using background markers revealed that genotype number 116 (BC3F1 Dodokan-Pup1+Alt), number 2 (BC3F1 Situ Bagendit-Pup1+Alt), and number 129 (BC3F1 Batur-Pup1+Alt) were the best genotypes with percentage of parent recovery of 95%, 90%, and 90.5%, respectively. These three genotypes were verified to have Alt loci and had the largest genetic proportion of restoring parents. Keywords: Alt, background markers, foreground markers, Pup1, upland rice